RECONSTRUCTING WOMANHOOD IN TONY MORRISON'S BELOVED - Suprajitno, Setefanus (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Tony Morrison's fifth novel, Beloved (1987), explores the degradation of slavery imposed upon slaves, even when they were owned by a "humane" slave master. The novel is set in the Reconstruction period, the period after the American civil war. The word reconstruction may be used for the Afro-Americans, especially for the Afro-American women who face double discrimination for being black and women. In dealing with women's oppression, Afro-American women have to reconstruct themselves as an act of survival, and to be aware of the horrors of the experiences which their ancestors had to go through.